Maternal Exposure to Air Pollution and Birth Outcomes - Malmqvist, Ebba (National Institute of Environmental Health Sciences, 2011)
BACKGROUND: The knowledge about air pollution effects on birth weight, prematurity, and small for gestational age (SGA) in low-exposure areas is insufficient. OBJECTIVES: The aim of this birth cohort study was to investigate whether low-level exposure to air pollution was associated with prematurity and fetal growth and whether there are sex-specific effects. METHOD: We combined high-quality registry information on 81,110 births with individually modeled exposure data at residence for nitrogen oxides (NO(x)) and proximity to roads with differing traffic density. The data were analyzed by logistic and linear regression with and without potential confounders. RESULTS: We observed an increased risk for babies being SGA when we compared highest and lowest NO(x) quartiles, adjusting for maternal age, smoking, sex, and year of birth. After additional adjustment for maternal country of origin and parity (which were highly intercorrelated), the increase was no longer statistically significant. However, in subgroup analyses when we compared highest and lowest NO(x) quartiles we still observed an increased risk for SGA for girls [odds ratio (OR) = 1.12; 95% confidence interval (CI), 1.01–1.24); we also observed increased risk among mothers who had not changed residency during pregnancy (OR = 1.09; 95% CI, 1.01–1.18). The confounders with the greatest impact on SGA were parity and country of origin. Concerning prematurity, the prevalence was lower in the three higher NO(x) exposure quartiles compared with the lowest category. CONCLUSION: For future studies on air pollution effects on birth outcomes, careful control of confounding is crucial.